Kemampuan Ibu Melakukan Stimulasi Untuk Perkembangan Bayi Usia 3-6 Bulan Di Wilayah Kerja Puskesmas Puhjarak - Riska Destiana; Erna Rahma Yani; Triatmi Andri Yanuarini (Akademi Keperawatan Dharma Husada Kediri, 2017)
Stimulation is one of the factors that affect a child’s development. The age of 3-6 months is included in the first 1000 days of life which is a critical period in which the child's brain begins to develop. Mothers can stimulate children according to their developmental stages. During infancy, a close relationship exists between the mother and child, so the influence of mother in educating the childis very big. The purpose of this study is to find out the correlation between the mothers ability to stimulate 3-6 months infant with their development in Puhjarak Community Health Center in Kediri Regency. The research desain used correlational study. The data collection was done by conducting cross sectional methods, with population of 38 mothers and their babies. The sampling used simple random sampling technique with total sample of 35 respondents who met the inclusion criteria. The analysis data used spearman rank showed p value 0,001. The conclution of this research was there was a correlation between mothers ability to stimulate 3-6 months infant with their development in Puhjarak Community Health Center Kediri Regency. It is advisable for parents especially mothers to maintain or improve their ability to stimulate their children in all aspects of development in a balanced and appropriate waywith the infant’s age.